Analisis Strategi Pasar dan Produk Pegadaian menggunakan Ansoff Matrix (Studi kasus pada Pegadaian Kantor Cabang Purwokerto) - Anisatul Amalia; Sutriawati Sutriawati; Siti Zakiyatul Fitriyah; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the ever-evolving digital era, financial service transformation is essential to increase company competitiveness. PT Pegadaian Purwokerto Branch as one of the State-Owned Enterprises (BUMN) has made various innovations in digital-based products and services are designed to address the requirements of the community, with particular emphasis on the lower middle class demographic. The study aims to analyze the market and product strategies implemented by Pegadaian Purwokerto Branch using the Ansoff Matrix approach. The research employed a qualitative descriptive methodology, utilizing data collection techniques that included direct interviews with branch office executives and comprehensive documentation. The data were subjected to analysis through the Ansoff Matrix framework, which encompasses four principal strategies: market penetration, market development, product development, and diversification. The results of the study show that Pegadaian Purwokerto Branch has implemented a market penetration strategy through service digitalization, product development by launching digital gold installment services and sharia financing, as well as a diversification strategy through collaboration with the e-commerce sector and other digital platforms. With this strategy, Pegadaian is expected to be able to maintain competitiveness and expand market reach sustainably.